2006
DOI: 10.1177/0363546506288753
|View full text |Cite
|
Sign up to set email alerts
|

Knee Angular Impulse as a Predictor of Patellofemoral Pain in Runners

Abstract: Footwear and running style can influence knee angular impulse, and the appropriate manipulation of these variables may play a preventive role for patients who are predisposed to patellofemoral pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 36 publications
4
143
2
2
Order By: Relevance
“…In fact, increased knee abduction moment with use of a medially wedged orthoses may be an undesirable effect based on previous research which identified knee abduction moment impulse as a potential risk factor for PFPS development among runners. 50 Therefore, although the effect to knee abduction moment in this study was small, a repeated exposure to these increased moments during a prolonged run may actually represent a mechanism for exacerbation of PFPS symptoms due to the use of medially wedged foot orthoses.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, increased knee abduction moment with use of a medially wedged orthoses may be an undesirable effect based on previous research which identified knee abduction moment impulse as a potential risk factor for PFPS development among runners. 50 Therefore, although the effect to knee abduction moment in this study was small, a repeated exposure to these increased moments during a prolonged run may actually represent a mechanism for exacerbation of PFPS symptoms due to the use of medially wedged foot orthoses.…”
Section: Discussionmentioning
confidence: 75%
“…This is not unprecedented: external knee-adduction moments have been previously reported in females during single-leg activities. 15,65 Although a prospective study 14 suggested that external knee-abduction moments best predict ACL injury risk, cadaveric data 13 indicated that ACL loads increase when either a 10-Nm external knee-abduction or -adduction moment is applied to the knee in the presence of an anterior tibial force. In the context of our findings, these cadaveric data suggest that kinetic changes at the knee as a consequence of an isolated hip-abductor fatigue protocol may actually reduce ACL loads during single-leg landings.…”
Section: Kinematic and Kinetic Datamentioning
confidence: 99%
“…9 studying the effects of sloped running on GRFs, noted that neither decline nor incline running affected normal active force peaks but that the impact peak of the vertical GRF increased during decline running. No authors have found a direct correlation between sloped running and injury risk, but it is worthwhile to recognize that changes in force demands on level surfaces have been suggested [11][12][13][14][15][16][17][18][19][20] to play a role in the development or progression (or both) of joint injury.…”
mentioning
confidence: 99%